A case of myopericarditis recurrence after third dose of BNT162b2 vaccine against SARS-CoV-2 in a young subject: link or causality?. (18th May 2022) - Mapelli, Massimo; Amelotti, Nicola; Andreini, Daniele; Baggiano, Andrea; Campodonico, Jeness; Moltrasio, Massimo; Majocchi, Benedetta; Mantegazza, Valentina; Vignati, Carlo; Ribatti, Valentina; Catto, Valentina; Sicuso, Rita; et al.
Abstract: The rate of post-vaccine myocarditis is being studied from the beginning of the massive vaccination campaign against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Although a direct cause–effect relationship has been described, in most cases, the vaccine pathophysiological role is doubtful. Moreover, it is not quite as clear as having had a previous myocarditis could be a risk factor for a post-vaccine disease relapse. A 27-year-old man presented to the emergency department for palpitations and pericardial chest pain radiated to the upper left limb, on the 4th day after the third dose of BNT162b2 vaccine. He experienced a previous myocarditis 3 years before, with full recovery and no other comorbidities. Electrocardiogram showed normal atrioventricular conduction, incomplete right bundle branch block, and diffuse ST-segment elevation. A cardiac echo showed lateral wall hypokinesis with preserved ejection fraction. Troponin-T was elevated (160 ng/L), chest X-ray was normal, and the SARS-CoV-2 molecular buffer was negative. High-dose anti-inflammatory therapy with ibuprofen and colchicine was started; in the 3rd day high-sensitivity Troponin I reached a peak of 23000 ng/L. No heart failure or arrhythmias were observed. A cardiac magnetic resonance was performed showing normal biventricular systolic function and abnormal tissue characterization suggestive for acute non-ischaemic myocardial injury (increased native T1 and T2 values, increased signal intensity at T2-weighted images and late gadolinium enhancement, all findings with matched subepicardial distribution) at the level of mid to apical septal, anterior, and anterolateral walls. A left ventricular electroanatomic voltage mapping was negative (both unipolar and bipolar), while the endomyocardial biopsy showed a picture consistent with active myocarditis. The patient was discharged in good clinical condition, on bisoprolol 1.25 mg, ramipril 2.5 mg, ibuprofen 600 mg three times a day, colchicine 0.5 mg twice a day. We presented the case of a young man with history of previous myocarditis, admitted with a non-complicated acute myopericarditis relapse occurred 4 days after SARS-CoV-2 vaccination (3rd dose). Despite the observed very low incidence of cardiac complications following BNT162b2 administration, and the lack of a clear proof of a direct cause–effect relationship, we think that in our patient this link can be more than likely. In the probable need for additional SARS-CoV-2 vaccine doses in the next future, studies addressing the risk-benefit balance of this subset of patient are warranted. We described a multidisciplinary management of a case of myocarditis recurrence after the third dose of SARS-CoV-2 BNT162b2 vaccine.